2020
DOI: 10.1038/s41419-019-2203-z
|View full text |Cite
|
Sign up to set email alerts
|

BCL-XL expression is essential for human erythropoiesis and engraftment of hematopoietic stem cells

Abstract: The anti-apoptotic BCL-2 proteins (BCL-2, BCL-XL, MCL-1, A1, BCL-W) counteract apoptotic signals emerging during development and under stress conditions, and are thus essential for the survival of every cell. While the "BCL-2 addiction" of different cell types is well described in mouse models, there is only limited information available on the role of different anti-apoptotic BCL-2 proteins in a given human cell type. Here we characterize the role of BCL-XL for survival and function of human hematopoietic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 54 publications
(68 reference statements)
2
30
0
Order By: Relevance
“…Thus, future studies are needed to gain mechanistic insights into how the described conditions influence platelet production. A recent paper reported a major role for Bcl-xL in human erythropoieisis and hematopoietic stem cells [ 77 ]; they also reported that Bcl-xL knockdown negatively impacted human megakaryocyte survival, albeit not significantly. Our unpublished results confirm that Bcl-xL knockdown impair human megakaryocyte survival, at early and later stages of their differentiation (personal data).…”
Section: Role Of Bcl-xl In Megakaryocyte Survivalmentioning
confidence: 99%
“…Thus, future studies are needed to gain mechanistic insights into how the described conditions influence platelet production. A recent paper reported a major role for Bcl-xL in human erythropoieisis and hematopoietic stem cells [ 77 ]; they also reported that Bcl-xL knockdown negatively impacted human megakaryocyte survival, albeit not significantly. Our unpublished results confirm that Bcl-xL knockdown impair human megakaryocyte survival, at early and later stages of their differentiation (personal data).…”
Section: Role Of Bcl-xl In Megakaryocyte Survivalmentioning
confidence: 99%
“…Bcl-2 proteins have also been shown to have a direct link to actin-mediated apoptosis as the pro-survival Bcl-X L protein suppresses apoptosis induced via cytochalasin D in Jurkat cells (48). Moreover, increased Bcl-X L expression is required for survival of differentiating erythroid cells (49). One can speculate that loss of an actin capping protein such as Tmod3 might act as a trigger for activation of signaling cascades leading to abrogation of increase in Bcl-X L expression, culminating in erythroid cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-xL is a critical anti-apoptotic protein that plays a role in normal embryogenesis, human erythropoiesis and promotes the survival of differentiating pancreatic cells [ 357 , 358 , 359 ]. Apoptosis is promoted when Bcl-xL residues Thr47 and Thr115 are phosphorylated in human myeloid leukemia cells by stress-activated JNK [ 360 ].…”
Section: Mitochondrial Kinases In Apoptosismentioning
confidence: 99%